PI(3,4)P2 Signaling in Cancer and Metabolism - Gozzelino, Luca; De Santis, Maria Chiara; Gulluni, Federico; Hirsch, Emilio; Martini, Miriam (Frontiers in Oncology, 2020)
The Phosphatidylinositide 3 kinases (PI3Ks) and their downstream mediators AKT and mammalian target of rapamycin (mTOR) are central regulators of glycolysis, cancer metabolism and cancer cell proliferation. At the molecular level, PI3K signaling involves the generation of the second messenger lipids phosphatidylinositol 3,4,5-trisphosphate (PI(3,4,5)P3) and phosphatidylinositol 3,4-bisphosphate (PI(3,4)P2). There is increasing evidence that PI(3,4)P2 is not only the waste product for the removal of PI(3,4,5)P3, but can act as a signaling molecule. Selective cellular functions for PI(3,4)P2 independent of PI(3,4,5)P3 have been recently described, including the clathrin-mediated endocytosis and mTOR regulation. However, the specific spatiotemporal dynamics and signaling role of PI3K minor lipid messenger PI(3,4)P2 are not well understood. This review aims at highlighting the biological functions of this lipid downstream of phosphoinositide kinases and phosphatases and its implication in cancer metabolism.